(untitled) (International Journal of Environmental Sciences, 2025)
We evaluated the performance of high resolution Ultrasound imaging in detecting proximal caries in primary posterior teeth, compared to bitewing (BW) radiography. A total of 64 deciduous molar teeth with proximal dentin caries (32 primary caries and 32 secondary caries under restorations) and 64 primary molar teeth without caries were used. All teeth were randomly placed in the |alveolar sockets of a dry skull in groups of 8. Digital intraoral bitewing radiographs were obtained by photostimulable phosphor plate (PSP) detector. US examinations were performed by using high-resolution ultrasonography (US). Finally, 2 image sets were obtained: 1) PSP bitewing radiography, and 2) HD US images. Images were viewed by 2 observers. Histology was considered as gold standard. Intraclass correlation coefficients (ICCs) were calculated to assess observer agreement. The areas under the ROC curves (AUC - Area Under Curve - values) and chi-square tests were utilized (α = 0.05). Higher intra-and inter-observer coefficients were found for primary caries compared to secondary caries and for bitewing radiography when compared to Ultrasound images. In general, excellent ICC values were calculated. Highest AUC values were found for bitewing radiography images for primary caries detection and lowest for Ultrasound images for secondary caries detection. Dual Diagnostic Performance Comparison between Ultrasound and bitewing radiography showed no statistically significant difference (P=0,329). Again, no statistically significant difference was found for diagnostic performance between primary and secondary caries detection (P=0,545). High resolution ultrasound imaging has the potential to be utilized in the detection of proximal dental caries in deciduous teeth.